Efficacy of Eribulin mesylate in older patients with breast cancer: A pooled analysis of clinical trial and real-world data. Issue 6 (July 2020) - Pedersini, Rebecca; di Mauro, Pierluigi; Amoroso, Vito; Parati, Maria Chiara; Turla, Antonella; Ghilardi, Mara; Vassalli, Lucia; Ardine, Mara; Volta, Alberto Dalla; Monteverdi, Sara; Borgonovo, Karen; Ghidini, Antonio; et al.
Abstract: Purpose: Eribulin mesylate (EM) is a non-taxane microtubule inhibitor approved for use in patients with metastatic breast cancer. With this pooled analysis of retrospective studies, we evaluated the efficacy and toxicity profile of EM in older patients with breast cancer in the real-world setting. Methods: We performed a systematic database search for studies published up to March 2019 and reporting outcome and adverse events with EM in older patients (≥70 years). Overall survival (OS), progression-free survival (PFS), and overall response rate (ORR) were described and aggregated in a pooled analysis. Main toxicity rates (G1–2 and G3–4) were also described. Results: The analysis included five studies for a total of 301 patients. The median age was 71 to 74 years. Pooled ORR, median PFS and OS were 23.2%, 4.8 and 13.1 months, respectively. The disease control rate was 47%. Grade 3–4 neutropenia was 0 to 49%, G3–4 anemia and thrombocytopenia were rare. The most frequent G3–4 adverse events among non-hematological toxicities were fatigue (5–16.5%) and neurotoxicity (0–10.1%). Dose reduction rate was reported in three studies and carried out in 40% of patients (18.6–84%). Conclusions: This pooled analysis shows that the median OS in older patients with breast cancer is 13 months, with an ORR of 23%. Control of disease was achieved in about 50% of patients. Dose reduction was relatively frequent and severe toxicities were rare. EM treatment of older patients with breast cancer is feasible and reflects the outcomes for the general population.